2016
DOI: 10.1103/physrevb.94.035440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen contamination on monolayer GeSe: A computational study

Abstract: Natural oxidation is a common degradation mechanism of both mechanical and electronic properties for most of the new two-dimensional materials. From another perspective, controlled oxidation is an option to tune material properties, expanding possibilities for real-world applications. Understanding the electronic structure modifications induced by oxidation is highly desirable for new materials like monolayer GeSe, which is a new candidate for near-infrared photodetectors. By means of first-principles calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…As another 2D semiconductor family material, binary IV-VI chalcogenides MXs (SnS, SnSe, SnTe, GeS, GeSe, and GeTe) have a proper bandgap (0.86-1.79 eV) that coincides with the range of visible light. 4,5 Similar to more recently studied BP, ML MXs have pucker structures, issuing in an in-plane anisotropic mechanical, electrical, and optical properties. [6][7][8] Compared with isotropic materials, an anisotropic material has an effective mass anisotropy, such as ML BP has a small effective mass (along the armchair direction) and a large effective mass (along the zigzag direction).…”
Section: Introductionmentioning
confidence: 74%
“…As another 2D semiconductor family material, binary IV-VI chalcogenides MXs (SnS, SnSe, SnTe, GeS, GeSe, and GeTe) have a proper bandgap (0.86-1.79 eV) that coincides with the range of visible light. 4,5 Similar to more recently studied BP, ML MXs have pucker structures, issuing in an in-plane anisotropic mechanical, electrical, and optical properties. [6][7][8] Compared with isotropic materials, an anisotropic material has an effective mass anisotropy, such as ML BP has a small effective mass (along the armchair direction) and a large effective mass (along the zigzag direction).…”
Section: Introductionmentioning
confidence: 74%
“…Previous calculations have indicated that oxidation could lead to severe local deformation on monolayer GeSe, and thus affecting the optoelectronic properties. 46 Herein, time-dependent Raman spectrum measurements were performed to examine the possible oxidation of GeSe nanosheets in air. For Raman characterizations, GeSe nanosheets were first loaded on the membrane filter and then exposed in air for various times.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Usually, the degradation of mechanical and electronic properties of the most 2D materials is caused by the oxidation under ambient conditions. Previous calculations have indicated that oxidation could lead to severe local deformation on monolayer GeSe, and thus affecting the optoelectronic properties . Herein, time-dependent Raman spectrum measurements were performed to examine the possible oxidation of GeSe nanosheets in air.…”
Section: Resultsmentioning
confidence: 99%
“…Analogues to black phosphorus, the large bonding anisotropy of their layered crystals can be considered as a distorted NaCl structure, which lead to a strong anisotropy in electronic band structures . However, unlike phosphorene, GeSe surface is much more stable and resistant to oxidation . Earth abundant and environmental friendship make GeSe particularly attractive in applications of semiconductors .…”
Section: Introductionmentioning
confidence: 99%